2017
DOI: 10.1126/sciadv.1601667
|View full text |Cite
|
Sign up to set email alerts
|

Fully gapped superconductivity with no sign change in the prototypical heavy-fermion CeCu 2 Si 2

Abstract: Heavy electrons with extremely strong Coulomb repulsions can condense into a fully gapped s-wave superconducting state.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 58 publications
3
69
0
1
Order By: Relevance
“…Another recent report [130] involving specific heat, thermal conductivity, and penetration depth measurements on CeCu2Si2 down to 0.06 K also found behavior consistent with non-nodal behavior: both C and  varied exponentially with temperature at low T and thermal conductivity /T  0 (no linear term). Contrasting with the modelling of Kittaka et al [50] and Yamashita et al [130] The final resolution of these new low temperature results, which imply nodeless behavior, requires some further time to digest and analyze the data. It would certainly be a surprise if the first UcS in the end was determined to have s-wave symmetry.…”
Section: Heavy Fermion Superconductors Withmentioning
confidence: 61%
“…Another recent report [130] involving specific heat, thermal conductivity, and penetration depth measurements on CeCu2Si2 down to 0.06 K also found behavior consistent with non-nodal behavior: both C and  varied exponentially with temperature at low T and thermal conductivity /T  0 (no linear term). Contrasting with the modelling of Kittaka et al [50] and Yamashita et al [130] The final resolution of these new low temperature results, which imply nodeless behavior, requires some further time to digest and analyze the data. It would certainly be a surprise if the first UcS in the end was determined to have s-wave symmetry.…”
Section: Heavy Fermion Superconductors Withmentioning
confidence: 61%
“…In contrast to this, recent experiments which have combined specific heat [8], penetration depth, and thermal conductivity measured down to very low temperatures have shown that gap nodes do not exist at any point on the Fermi surface of CeCu 2 Si 2 [1]. This nodeless structure might still be explained by a spin-fluctuation mechanism if the points in k-space where the gap changes sign do not coincide with the Fermi surface sheets, as is the case for most iron-pnictide materials.…”
mentioning
confidence: 87%
“…[28]. To minimize errors due to geometrical demagnetization factors we measured the same sample both before and after irradiation with a dose of 1.9 C=cm 2 , which reduced T c from 0.64 to 0.52 K. For the irradiated sample we found μ 0 H c1 ¼ 0.9 AE 0.1 mT at 100 mK compared to μ 0 H c1 ð0Þ ¼ 1.8 AE 0.1 mT in the pristine sample [1]. From this we estimate that λð0Þ is increased from 700 AE 50 nm for the unirradiated sample to 1100 AE 100 nm for the irradiated one.…”
mentioning
confidence: 99%
“…Even so, a fundamental question is why the high-T c plain s-wave state appears against the repulsive interaction by spinfluctuations. More surprisingly, the plain s-wave state is reported in heavy-fermion superconductor CeCu 2 Si 2 near the magnetic phase, according to the measurements of the specific heat, penetration depth, thermal conductivity, and electron irradiation effect on T c [11,12].Therefore, it is a significant problem for theorists to establish a general mechanism of the plain s-wave superconductivity in strongly correlated electron systems. One important feature of these s-wave superconductors would be the orbital degrees of freedom.…”
mentioning
confidence: 99%
“…Even so, a fundamental question is why the high-T c plain s-wave state appears against the repulsive interaction by spinfluctuations. More surprisingly, the plain s-wave state is reported in heavy-fermion superconductor CeCu 2 Si 2 near the magnetic phase, according to the measurements of the specific heat, penetration depth, thermal conductivity, and electron irradiation effect on T c [11,12].…”
mentioning
confidence: 99%